THE SERVICE PERFORMANCE OF PUBLIC TRANSPORTATION TYPE OF MOTOR VEHICLE TESTING IN TRANSPORTATION SERVICE OF SUKOHARJO REGENCY - Adhi Latief Sallimi (Solidaritas, 2018)
ABSTRACT This research aimed to describe the Service Performance of Public Transportation Type of Motor Vehicle Testing in Transportation Service of Sukoharjo Regency using 11 indicators of service performance that that were then simplified by the author into some sub indicators of service performance.This study was a qualitative research. Techniques of collecting data used were direct interview with service users and service providers and documentation. The types of data used were primary and secondary ones; the informants were selected with certain consideration, those actually know the problems or called key informants. The result of research showed that the service performance of motor vehicle testing in Transportation Service of Sukoharjo Regency, viewed from tangibility, had been adequate despite some weaknesses regarding less broad waiting room regarding security, there had been 2 security guards in transportation service of Sukoharjo Regency, but in vehicle testing, there had been no security guard.Keywords: Performance, Service, Credibility, Responsiveness